Durian shell active ingredient nanocellulose antibacterial fresh-keeping coating and preparation method
Through the extraction and compounding of the active ingredient nanocellulose of durian shell, an antibacterial and fresh preservation coating was prepared, which solved the problem of fungal disease control after fruit and vegetable harvesting, and achieved a safe, environmentally friendly and low-cost fruit and vegetable preservation effect.
Patent Information
- Application Number
- CN202411517867.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The prior art is difficult to effectively control postharvest fungal diseases of fruits and vegetables, and traditional methods have problems of environmental pollution, health risks and high costs.
By using the active ingredient nanocellulose in the durian shell, an antibacterial fresh-preserving coating film was prepared. The nanocellulose was extracted by water extraction and acid hydrolysis, and combined with materials such as hydroxymethylcellulose to form a coating film with antibacterial activity.
This coating is not only biodegradable, safe and non-toxic, but also has significant effects on preserving fruits and vegetables after harvesting. It can delay the fruit maturation process, reduce quality loss, and significantly inhibit pathogenic bacteria such as Fusarium oxysporus and Penicillium.
Smart Images

Figure CN119032989B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of food preservation, and relates to a nano-cellulose antibacterial fresh-keeping coating film with active ingredients of durian shell and a preparation method thereof. Background Art
[0002] Penicillium expansum is one of the main pathogens that cause post-harvest fungal diseases of fruits. It not only causes penicillium disease in fruits, but also secretes patulin, which has acute and chronic toxicity and can cause convulsions, ulcers, intestinal inflammation, vomiting, and DNA damage to the brain, liver and kidneys, seriously endangering human health.
[0003] Therefore, it is necessary to find a safe and efficient method to control postharvest Penicillium disease in fruits. At present, the use of natural active ingredients to develop active coatings with fruit preservation capabilities has become an important means of economical, safe and efficient postharvest fruit disease prevention and preservation storage.
[0004] Durian is the "king of fruits" and is loved by consumers. Durian shell accounts for two-thirds of the weight of the entire durian. As agricultural waste, the large amount of durian shell accumulation has caused a great environmental burden. Durian shell is rich in active substances, cellulose and other biomass resources that have not been fully explored and utilized.
[0005] Durian shell has a cellulose content of up to 60.5%, and contains multiple components such as hemicellulose and lignin, making it a very promising cellulose resource. However, the current research on the reuse of durian shell, its relative utilization rate and application are very limited.
[0006] Durian shell contains a variety of bioactive substances, such as polyphenols, flavonoids and polysaccharides, which are considered to be potential sources of natural antioxidants. These components can participate in the synthesis of nanoparticles as reducing agents and stabilizers.
[0007] Worldwide, postharvest fruits and vegetables are susceptible to infection by different fungal pathogens, resulting in postharvest corruption and waste. For a long time, people have conducted extensive research on postharvest disease control methods for fruits and vegetables, which are divided into three categories: physical, chemical, and biological. Among them, the physical method is relatively expensive and will inevitably cause irreversible damage to the quality of fruits and vegetables; in the chemical method, the use of traditional fungicides is likely to cause problems such as increased pathogen resistance and drug residues, which endanger the environment and human health; in the biological method, the application conditions of biocontrol agents are relatively high and the actual application is relatively limited, making it difficult to be used on a large scale.
[0008] Therefore, safe, pollution-free, low-cost and non-damaging methods for fruit and vegetable quality have become promising and effective strategies for controlling fruit and vegetable pathogens. Plasticizers improve the flexibility of coatings, emulsifiers and surfactants improve the adhesion of coatings, antioxidants improve the storage and functionality of coatings, and bioactive ingredients improve the antibacterial activity of coatings. Among bioactive ingredients, plant extracts have always attracted the attention of domestic and foreign researchers due to their wide sources, low costs, safety and effectiveness. Summary of the invention
[0009] The invention aims to provide a nanocellulose antibacterial fresh-keeping coating film with active ingredients of durian shell and a preparation method thereof, which can be widely used for the post-harvest fresh-keeping of fruits.
[0010] To achieve the above object, the technical solution of the present invention is: as a first aspect, a method for preparing a nanocellulose antibacterial fresh-keeping coating film containing active ingredients of durian shell is provided, comprising the following steps:
[0011] (1) taking durian shell, drying it to prepare durian shell powder; treating the durian shell powder by water extraction to extract active ingredients from the durian shell, and freeze-drying the supernatant to obtain a water extract powder containing the active ingredients from the durian shell;
[0012] (2) treating the durian shell powder with alkaline water extraction to obtain a precipitate, collecting the precipitate, freeze-drying, bleaching, repeatedly washing the precipitate with water until the pH value of the filtrate is neutral, and drying to obtain durian shell cellulose; treating the durian shell cellulose with acid hydrolysis to obtain a precipitate, dispersing the precipitate in water, and dialyzing it until the pH value is neutral; after the dialysis is completed, ultrasonic treatment is performed, and freeze-drying is performed to obtain nanocellulose powder;
[0013] (3) Take sodium hydroxymethyl cellulose, add water, glycerol, and nanocellulose powder in sequence, and stir continuously at 70°C for 2 h to obtain the first film-forming solution;
[0014] (4) adding the water extract powder containing the active ingredient of durian shell to the first film-forming liquid at a solid-liquid ratio of 0.02-0.10 g / mL, stirring continuously at 70°C for 10 min to obtain the second film-forming liquid, and preparing a film to obtain the durian shell active ingredient nanocellulose antibacterial fresh-keeping coating;
[0015] The ratio of sodium hydroxymethyl cellulose, water, glycerin and nanocellulose powder is 1 g: 500 mL: 0.3 g: 0.01-0.1 g.
[0016] Furthermore, the alkali washing is specifically as follows: adding the precipitate obtained after treating the durian shell powder by water extraction into a NaOH solution with a concentration of 0.04 g / mL, water bathing at 90°C, and continuously stirring for 2 hours, collecting the precipitate, washing with water, filtering, and centrifuging to remove excess alkali solution, and collecting the precipitate; repeating the above process until the supernatant after centrifugation is colorless; the concentration of the durian shell powder in the NaOH solution is 0.04 g / mL.
[0017] Furthermore, the bleaching is specifically as follows: adding the dried precipitate to a bleaching solution, placing in a water bath at 80° C., continuously stirring for 2 h, filtering, and collecting the precipitate; repeating the above process until the precipitate is white; the concentration of the dried precipitate in the bleaching solution is 0.04 g / mL.
[0018] Furthermore, the bleaching solution consists of 0.017 g / mL NaClO, 0.027 g / mL NaOH, and 0.075 g / mL glacial acetic acid.
[0019] Furthermore, the acid hydrolysis method is specifically as follows: adding durian shell cellulose to a sulfuric acid solution with a volume concentration of 62% (v / v) so that the concentration of the durian shell cellulose in the sulfuric acid solution is 0.067 g / mL, and hydrolyzing in a 45°C water bath for 30 min; adding water to terminate the reaction, centrifuging, removing the supernatant, and collecting the precipitate.
[0020] Furthermore, the dialysis treatment specifically includes: dispersing the precipitate with water and then placing it into a dialysis bag for dialysis treatment until the pH value is neutral.
[0021] Furthermore, the ultrasonic treatment is specifically carried out under ice water bath conditions, with a power of 600 W, a time of 60 min, and an ultrasonic process of 1 s on and 1 s off.
[0022] Furthermore, the freeze drying is specifically: freezing at -80°C for 12 hours, and then drying in a freeze dryer for 48 hours.
[0023] Furthermore, the water extraction method is used to treat durian shell powder, freeze-dry it, and obtain a water extract powder containing active ingredients from durian shell. Specifically, water is added to the durian shell powder so that the solid-liquid ratio of durian shell powder to water is 1g:55ml, and the mixture is extracted in a water bath at 90°C for 1 hour, and then ultrasonically maintained at 90°C and 100W for 90 minutes; centrifugation is performed to collect the supernatant, and the supernatant is filtered to obtain a filtrate, which is then rotary evaporated at 70°C for at least 1 hour until no water vapor is evaporated to obtain a paste-like water extract, which is frozen at -80°C for 12 hours, and then dried in a freeze dryer for 48 hours to obtain a water extract powder containing active ingredients from durian shell.
[0024] As a second aspect, the present invention also provides an antibacterial and fresh-keeping coating of nanocellulose containing active ingredients of durian shells prepared by the preparation method.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0026] (1) The present invention uses waste durian shell as the main principle to prepare the nanocellulose antibacterial and fresh-keeping coating film with active ingredients from durian shell. Durian shell is widely available and renewable, which provides a new path for the reuse of durian shell and reduces the pollution of durian shell to the environment.
[0027] (2) The durian shell and nanocellulose used in the present invention are both environmentally friendly and degradable natural substances. The nanocellulose antibacterial fresh-keeping coating made from the active ingredient of durian shell has good biodegradability, is safe and non-toxic, and has a good effect on the preservation of fruits after harvest. It can delay the ripening process of apple fruits after harvest, reduce quality loss, and extend the shelf life of apple fruits;
[0028] (3) The antibacterial and fresh-keeping coating process of nanocellulose, an active ingredient in durian shell, is simple and easy, has good film-forming properties, is low in cost, and is pollution-free. It also has good crystallinity, hydrophobicity, mechanical properties, and barrier properties, which will be enhanced with the increase of nanocellulose content;
[0029] (4) The nanocellulose antibacterial fresh-keeping coating containing active ingredients from durian shell has a good antibacterial effect and has a significant inhibitory effect on Fusarium oxysporum, Penicillium expansum, etc.; applying the nanocellulose antibacterial fresh-keeping coating containing active ingredients from durian shell to apples can effectively prevent apple penicillium disease caused by Penicillium expansum. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The cross-sectional SEM images of the composite membranes at different CNC concentrations, where (A) is the cross-sectional SEM image of 0% CNC, (B) is the cross-sectional SEM image of 1% CNC, (C) is the cross-sectional SEM image of 3% CNC, (D) is the cross-sectional SEM image of 5% CNC, (E) is the cross-sectional SEM image of 7% CNC, and (F) is the cross-sectional SEM image of 10% CNC;
[0031] Figure 2 is the XRD pattern of the composite film at different CNC concentrations;
[0032] Figure 3 FTIR spectra of composite films at different CNC concentrations;
[0033] Figure 4WCA graphs of composite membranes under different CNC concentrations; (A) is the WCA graph of the composite membrane under 0% CNC, with a WCA of 37.6 ± 0.6°, (B) is the WCA graph of the composite membrane under 1% CNC, with a WCA of 40.0 ± 4.9°, (C) is the WCA graph of the composite membrane under 3% CNC, with a WCA of 55.7 ± 1.8°, (D) is the WCA graph of the composite membrane under 5% CNC, with a WCA of 76.5 ± 0.9°, (E) is the WCA graph of the composite membrane under 7% CNC, with a WCA of 80.0 ± 0.6°, and (F) is the WCA graph of the composite membrane under 10% CNC, with a WCA of 84.1± 0.9°;
[0034] Figure 5 is the WVP diagram of the composite membrane at different CNC concentrations;
[0035] Figure 6 The inhibitory effect of DSWE on Penicillium expansum, where (A) is a schematic diagram of the colony diameter of the PDA, 75% ethanol, and 10% DSWE groups, and (B) is a graph showing the growth of Penicillium expansum in the 0%, 0.0625%, 0.125%, 0.25%, 0.5%, 1%, and 2% DSWE groups after 3 and 8 days.
[0036] Figure 7 The inhibitory effect of different concentrations of DSWE on Fusarium oxysporum is shown in Figure 2, where (A) is the change of colony diameter in the 0, 0.1%, 0.2%, and 0.4% DSWE groups, and (B) is the growth of Fusarium oxysporum after 2d, 3d, 4d, 5d, and 6d.
[0037] Figure 8 The following are the apple quality evaluation diagrams of the fresh group, CK, CG, and DCCG groups; (A) is the color difference comparison diagram of each group after 5 and 10 days of storage, (B) is the chromaticity comparison diagram, (C) is the hue comparison diagram, (D) is the total phenol content comparison diagram, (E) is the weight loss rate comparison diagram, (F) is the soluble solid content comparison diagram; (G) is the titratable acid content comparison diagram, and (H) is the hardness comparison diagram;
[0038] Fig. 9 The effect of DSWE-CNC coating on the pathogenicity of Penicillium expansum, where (A) is a comparison of the lesion diameters of PC, NC, 0% DSWE group, 2% DSWE group, 4% DSWE group, and 10% DSWE group; (B) is a comparison of the incidence of apples; (C) is a schematic diagram of apple inoculation and the disease status of apples after 3d, 4d, and 5d;
[0039] Fig.10These are SEM images of durian shell powder (DS) and durian shell nanocellulose (CNC), where (A) is the SEM image of DS and (B) is the SEM image of CNC. DETAILED DESCRIPTION
[0040] In order to have a better understanding of the technical features, purposes and beneficial effects of the present invention, the following is a detailed description of the present invention in conjunction with the accompanying drawings. The present invention is further described in the following embodiments, but the present invention is not limited to the embodiments.
[0041] The present invention firstly detects, analyzes and studies the antibacterial inhibition of the components of the active ingredient of durian shell (DSWE), then prepares and characterizes durian shell nanocellulose and its composite film, and finally prepares the antibacterial fresh-keeping coating of the active ingredient of durian shell nanocellulose, confirming its potential application in the post-harvest preservation of apples. The development of new fruit and vegetable preservatives using durian shells has important research significance and application value, which not only provides new ideas for the green recycling of durian shells, but also provides theoretical support for the application of durian shells in the post-harvest preservation of fruits.
[0042] The nanocellulose antibacterial and fresh-keeping coating film with active ingredients of durian shell described in the present invention is made of durian shell as raw material, and nanocellulose is extracted by sulfuric acid hydrolysis. Then, sodium carboxymethyl cellulose is used as a matrix, and nanocellulose in different proportions is compounded to prepare a nanocellulose composite film. The present invention uses sulfuric acid hydrolysis to extract nanocellulose in durian shell. After sulfuric acid hydrolysis and ultrasound, the Zeta potential of cellulose decreases from -0.007 mV to -25.7 mV. Sulfuric acid hydrolysis introduces negatively charged sulfonic acid groups on the surface of durian shell nanocellulose, and ultrasonic treatment allows the nanocellulose suspension to be fully dispersed, which promotes more contact between CNC and oxygen, resulting in oxidation of the particle surface, thereby generating more negative charges.
[0043] Example 1: Step 1, preparation of nanocellulose powder: water extraction treatment of durian shell powder, freeze drying of the supernatant, and obtaining water extract powder containing active ingredients of durian shell; adding the precipitate obtained after water extraction treatment of durian shell powder to a NaOH solution with a concentration of 0.04 g / mL, so that the concentration of the durian shell powder in the NaOH solution is 0.04 g / mL, and stirring is continued for 2 h in a 90°C water bath environment. After stirring, the precipitate collected by filtration is washed with deionized water, and then centrifuged (10000 rpm, 10 min) to remove excess alkali solution, and the precipitate is collected. The alkali washing process is repeated 4-5 times until the supernatant after centrifugation is nearly colorless. After the alkali washing is completed, the precipitate is placed in a freeze dryer and dried for 48 h, and then bleached. The bleaching treatment is specifically as follows: the dried precipitate is added to the bleaching solution so that the concentration of the dried precipitate in the bleaching solution is 0.04 g / mL, and the precipitate is continuously stirred for 2 hours in an 80°C water bath environment, and the precipitate is collected by filtration. This rinsing process is also repeated 4-5 times until the precipitate is white. The bleaching solution is composed of 0.017 g / mL NaClO, 0.027 g / mL NaOH, and 0.075 g / mL glacial acetic acid. Finally, the precipitate is repeatedly washed with deionized water until the pH of the filtrate is neutral, and then dried to obtain durian shell cellulose.
[0044] The durian shell cellulose was added to a sulfuric acid solution with a volume concentration of 62%, so that the concentration of the durian shell cellulose in the sulfuric acid solution was 0.067 g / mL, and hydrolyzed in a water bath at 45°C for 30 min (referred to as the first reaction solution). After the hydrolysis was completed, deionized water with a volume (v / v) of 10 times that of the first reaction solution was immediately added to terminate the reaction, and then centrifuged (10000 rpm, 10 min) to remove the supernatant and collect the precipitate.
[0045] The precipitate was dispersed with deionized water and placed in a dialysis bag for dialysis treatment until the color of the liquid in the dialysis bag was stable and no longer changed (indicating that the pH was neutral). After the dialysis was completed, the first nanocellulose suspension was obtained and stored at 4°C for future use.
[0046] Under ice water bath conditions (0°C in this embodiment), a titanium ultrasonic probe with a diameter of 5 mm was inserted into the beaker containing the first nanocellulose suspension to ensure that the liquid level was 20 mm above the probe. Then, ultrasonic treatment was performed at a power of 600 W for 60 min, with an ultrasonic process of 1 s on and 1 s off. After the ultrasonic treatment, a second nanocellulose suspension was obtained and stored at 4°C for future use. The second nanocellulose suspension was freeze-dried to obtain nanocellulose powder, which was stored at 4°C for future use. DS and CNC were observed by scanning electron microscopy (SEM), as shown in FIG. Fig.10 As shown in (A) and (B).
[0047] Step 2, preparation of nanocellulose composite membrane: sodium hydroxymethylcellulose (CMC) was added to deionized water at a solid-liquid ratio of 1:500 (g / ml), followed by glycerol (the mass ratio of sodium hydroxymethylcellulose to glycerol was 1:0.3), and then nanocellulose was added to form suspensions containing 0, 1%, 3%, 5%, 7% and 10% CNC (the mass ratio of nanocellulose to sodium hydroxymethylcellulose was 0, 1%, 3%, 5%, 7% and 10%, respectively). Stir continuously at 70°C for 2 h to prepare the first membrane-forming solution. The nanocellulose coating membrane-forming solution was prepared into a CNC composite membrane by solution casting.
[0048] Step 3, morphology of CNC composite films: After the composite films containing 0, 1%, 3%, 5%, 7%, and 10% CNC were gold-sprayed, their cross-sectional microstructures were observed by SEM.
[0049] Example 2: Step 1, preparation of nanocellulose powder: proceed according to step 1 of Example 1.
[0050] Step 2, preparation of nanocellulose composite membrane: proceed according to step 2 of Example 1.
[0051] Step 3, X-ray diffraction (XRD) analysis of CNC composite film: The crystal structure of the nanocellulose composite film (hereinafter referred to as film) was analyzed by XRD instrument. The CNC and film samples were spread on the sample slot and gently pressed to fill the sample slot. The measurement was performed under the conditions of a scanning range of 5° - 50° and a scanning speed of 5° / min.
[0052] Example 3: Step 1, preparation of nanocellulose powder: proceed according to step 1 of Example 1.
[0053] Step 2, preparation of nanocellulose composite membrane: proceed according to step 2 of Example 1.
[0054] Step 3: Fourier transform infrared spectroscopy (FTIR) analysis of CNC composite membrane: FTIR instrument was used to analyze the chemical group changes of nanocellulose and its composite membrane (hereinafter referred to as membrane). The film sample was mixed and ground with potassium bromide at a ratio of 1:100 (mass ratio), then pressed into sheets and irradiated in the infrared wavelength range of 500-4000 cm -1 Internal scanning.
[0055] Example 4: Step 1, preparation of nanocellulose powder: proceed according to step 1 of Example 1.
[0056] Step 2, preparation of nanocellulose composite membrane: proceed according to step 2 of Example 1.
[0057] Step 3, static water contact angle (WCA) of CNC composite membrane: The static water contact angle of nanocellulose composite membrane (hereinafter referred to as film) containing different concentrations of CNC was measured using a contact angle surface tension meter to analyze the hydrophobicity differences of nanocellulose composite membranes containing different concentrations of CNC. A high-precision syringe was used to gently place a drop of deionized water on the film, and the process was recorded by an optical contact angle device with a high-speed camera. The video was analyzed, and the time point when the deionized water droplet contacted the film was set to the 0th frame, and the image of the droplet in complete equilibrium on the film (nth frame) was captured. The subsequent videos were all captured at the same time point. Subsequently, the analysis software calculated the contact angle value.
[0058] Example 5: Step 1, preparation of nanocellulose powder: proceed according to step 1 of Example 1.
[0059] Step 2, preparation of nanocellulose composite membrane: proceed according to step 2 of Example 1.
[0060] Step 3, determination of mechanical properties of CNC composite film (hereinafter referred to as film): The thickness of the film was measured by a handheld digital micrometer (SanLiang, Japan). The measurement was performed at 5 different points on each sample and the average value was calculated.
[0061] Before mechanical property testing, the film samples were cut into rectangular strips with a size of 25 × 15 mm. The tensile strength (TS), elongation at break (EL) and ultimate modulus (UM) of the film were measured by a cellulose tensile instrument at a tensile rate of 50 mm / min. These three parameters determine the mechanical stability of the film. The initial holding distance was 25 mm.
[0062] Example 6: Step 1, preparation of nanocellulose powder: proceed according to step 1 of Example 1.
[0063] Step 2, preparation of nanocellulose composite membrane: proceed according to step 2 of Example 1.
[0064] Step 3, determination of water vapor permeability of CNC composite film (hereinafter referred to as film): Use the weight method to measure the water vapor permeability (WVP) value. The film is tightly attached to the top of a weighing bottle, which is filled with two-thirds of pre-dried anhydrous calcium chloride. Subsequently, the weighing bottle is weighed and stored in a sealed desiccator (18°C, 71% relative humidity) filled with a supersaturated NaCl solution, and the weighing bottle is weighed every 1 h for 12 h. The WVP formula of the film sample is as follows:
[0065] X = (Δm × d) / (Δt × A × ΔP);
[0066] Where: X is the WVP value (1×10 -11 g / m·s·Pa); Δm is the weight gain of the weighing bottle between the first and last measurements (g); d is the film thickness (mm); Δt is the time difference between the first and last measurements (s); A is the effective area of the film covering the mouth of the weighing bottle (m 2 ); ΔP is the water vapor pressure difference between the inside and outside of the film at 18°C (kPa).
[0067] Example 7: Step 1, extraction of active ingredients from durian shell: dry the durian shell to make a powder, take the durian shell powder, add deionized water to it at a solid-liquid ratio of 1:55 (g / ml), extract in a 90°C water bath for 1 h, and then ultrasonicate at 90°C and 100W for 90 min. Centrifuge to obtain the supernatant, filter the supernatant, and then rotary evaporate the filtrate at 70°C for at least 1 hour until no water vapor is evaporated to obtain a paste water extract. The obtained paste water extract was frozen at -80°C for 12 h, and finally dried in a freeze dryer for 48 h to obtain a water extract powder containing active ingredients from durian shell.
[0068] Step 2: Inhibitory effect of active ingredients from durian shell on the fungus Penicillium expansum: different amounts of water extract powder containing DSWE were added to glucose potato medium (PDA) to make the final concentrations 0%, 0.0625%, 0.125%, 0.25%, 0.5%, 1%, 2%, 6%, and 10% (mass ratio), respectively, and sterilized and poured into plates. Take 20 μL of Penicillium expansum spore suspension (1 × 10 5 spores / mL) were spread on PDA and cultured in a dark incubator at 25°C for 3 days to observe whether Penicillium expansum grew. The lowest concentration without hyphae growth was the minimum inhibitory concentration (MIC). Each treatment was repeated 3 times.
[0069] Step 3: Inhibitory effect of active ingredients from durian shell on Fusarium oxysporum: Using the hanging drop method, different amounts of water extract powder containing DSWE were added to PDA to make the final concentrations 0, 0.1%, 0.2%, and 0.4% (mass ratio), respectively. Sterilize and pour the plates. Take 5 μL of Fusarium oxysporum spore suspension (1 × 10 6 spores / mL) were dropped in the center of the PDA plate and cultured in the dark at 25°C for 2 days to observe the growth of Fusarium oxysporum. Each treatment was repeated 3 times.
[0070] Example 8: Step 1, preparation of nanocellulose powder: proceed according to step 1 of Example 1.
[0071] Step 2, extraction of active ingredients from durian shell: proceed according to step 1 of Example 7.
[0072] Step 3, preparation of DSWE-CNC film-forming liquid: take the first film-forming liquid containing 0.2% CMC and 3% (based on CMC mass) CNC (the ratio of sodium hydroxymethylcellulose, water, glycerol, and nanocellulose powder is 1 g: 500 mL: 0.3 g: 0.03 g), set up 0% DSWE group and 2% DSWE group respectively, wherein the 0% DSWE group does not add the water extract powder containing DSWE, and the 2% DSWE group adds the water extract powder containing DSWE, so that the solid-liquid ratio of the water extract powder containing DSWE to the first film-forming liquid is 0.02 g / mL, and the mixture is stirred and mixed at 70°C for 10 min. The second film-forming liquid prepared is the DSWE-CNC film-forming liquid. Film preparation, the antibacterial and fresh-keeping coating film of nanocellulose active ingredient of durian shell is obtained, wherein the coating film prepared by the 0% DSWE group is called CG, and the coating film prepared by the 2% DSWE group is called DCCG.
[0073] Step 4: Inoculate the DSWE-CNC film-forming solution on apples: soak the apples in 0.1% sodium hypochlorite for 1 min for disinfection, then wash with deionized water and dry. Subsequently, soak the apples in CG and DCCG for 5 min. After drying, transfer the apples to a fresh-keeping box, seal with plastic wrap and poke holes, then transfer the fresh-keeping box to a 25°C incubator for incubation for 10 days, and measure the weight loss rate, hardness, color difference, soluble solids and titratable acid of the apples on the 5th and 10th days respectively. Five apples were treated in each treatment, and each test was repeated 3 times.
[0074] Example 9: Step 1, preparation of nanocellulose powder: proceed according to step 1 of Example 1.
[0075] Step 2, extraction of active ingredients from durian shell: proceed according to step 1 of Example 7.
[0076] Step 3, preparation of DSWE-CNC film-forming solution: take a first film-forming solution containing 0.2% CMC and 3% (based on CMC content) CNC (the ratio of sodium hydroxymethyl cellulose, water, glycerol, and nanocellulose powder is 1 g: 500 mL: 0.3 g: 0.03 g), and set up DSWE of 0% DSWE group, 2% DSWE group, 4% DSWE group and 10% DSWE group respectively, wherein the 0% DSWE group and the 2% DSWE group are the same as Example 8, the 4% DSWE group is added with water extract powder containing DSWE, so that the solid-liquid ratio of the water extract powder containing DSWE to the first film-forming solution is 0.04 g / mL, the 10% DSWE group is added with water extract powder containing DSWE, so that the solid-liquid ratio of the water extract powder containing DSWE to the first film-forming solution is 0.10 g / mL, and the mixture is stirred and mixed at 70°C for 10 min. The prepared second film-forming solution is the DSWE-CNC film-forming solution.
[0077] Step 4: Effect of DSWE-CNC coating on the pathogenicity of Penicillium expansum: Soak the apples in 0.1% sodium hypochlorite for 1 min for disinfection, then wash with tap water and dry. Drill holes (6 mm × 2 mm) at the four corners and the center of the apple equator, and treat the wounds as follows: Fig. 9 As shown in (C): (1) 20 μL of commercial antibacterial agent (imazalil sulfate, Positive Control, PC) was added; (2) and (3) 20 μL of sterile water was added; (4) 20 μL of film-forming solution (0% / 4%) was added; (5) 20 μL of DSWE-CNC film-forming solution (2% / 10%) was added. Then, 10 μL of Penicillium expansum spore suspension (1 × 10 3 spores / mL), of which treatment (2) was inoculated (NC), treatment (3) was not inoculated (CK), and the rest were inoculated. After inoculation, the apples were placed in a fresh-keeping box and sealed with plastic wrap, and then incubated at 25°C for 5 days. Observation was performed every day, and the incidence of fruit wounds and lesion diameters were recorded after the disease occurred. The results were expressed as average lesion diameter (mm) and average incidence (%) to evaluate the incidence of apple blue mold. Each treatment had 12 apples, and each experiment was repeated 3 times.
[0078] Test Item 1: Characterization and analysis and comparison of membrane properties of pure cellulose membrane and composite membranes at different nanocellulose concentrations.
[0079] Samples were prepared according to Examples 1 to 6, and SEM, XRD, FTIR, WCA, mechanical properties, WVP and other indicators were analyzed and compared. The analysis results are as follows: Figures 1 to 5 and Table 1.
[0080] like Figure 1As shown in Figure 2, a large number of pores were observed in the cross-section of the 0% CNC composite film. With the addition of CNC, the microporous structure of the cross-section of the composite film decreased and became smoother. This phenomenon reflects the high compatibility between the CNC and CMC matrices, which is attributed to the nanoscale size of CNC, the chemical similarity between CNC and CMC, and the hydrogen bonding between CNC and CMC. In addition, too high a CNC concentration (5% - 10%, based on CMC content) will cause agglomeration due to uneven dispersion and no pore filling, which will affect the microstructure, integrity, mechanical properties, and water vapor barrier properties of the composite film.
[0081] Depend on Figure 2 It can be seen that the crystal structure of nanocellulose will not be destroyed by the interaction between sodium hydroxymethyl cellulose and nanocellulose, and the addition of CNC will increase the crystallinity of the CNC composite film.
[0082] Depend on Figure 3 It can be seen that the FTIR spectra of the composite films with different CNC concentrations have almost identical absorption peaks, indicating that no chemical reaction occurs between CMC and CNC during the film formation process. -1 and 1612.45 cm -1 The intensities of the two absorption peaks are significantly different, which correspond to the stretching vibrations of the intermolecular -OH groups, intermolecular and intramolecular hydrogen bonds, and the stretching vibrations of the carboxylic acid groups. In addition, with the increase of CNC content, the absorption peak intensities of the CNC composite film at these two locations are significantly enhanced, which is attributed to the rich hydroxyl groups in CNC.
[0083] Depend on Figure 4 It can be seen that the static water contact angle of the pure CMC film is 37.6°, indicating that the surface particles have strong hydrophilicity. With the increase of CNC content, the static water contact angle of the CNC composite film increases significantly, which means that CNC has good hydrophobicity, which is attributed to the hydrophobic (200) β crystal plane. When CNC with good hydrophobicity forms a composite film with CMC, it will be evenly dispersed on the surface of the composite film after stirring, so the hydrophobicity of the CNC composite film is improved.
[0084] Table 1 shows the thickness and mechanical properties of composite films with different CNC concentrations. The thickness of the composite film increases with the increase of CNC content, which is mainly due to the increase of solid content in the composite film. The mechanical strength of the composite film reflects the damage resistance of the composite film during transportation, storage and packaging applications. Among them, TS, UM and EL are the main mechanical performance parameters, which determine the mechanical stability of the film. The TS, UM and EL of the composite film increase with the increase of CNC content. Compared with the 0% CNC composite film, the TS, UM and EL of the 10% CNC composite film increased by 32.8%, 16.0% and 12.6%, respectively. TS reflects the maximum stress that the composite film can withstand before breaking, while UM determines the rigidity of the composite film. Their increase is attributed to the formation of intermolecular hydrogen bonds between CNC and CMC. The significant increase in EL indicates that the addition of CNC improves the toughness of the composite film, which is attributed to the formation of strong hydrogen bonds between CMC and glycerol caused by heating, stirring and plasticization.
[0085] Table 1 Thickness and mechanical properties of different CMC / CNC composite films
[0086]
[0087] All values are expressed as mean ± standard deviation, and different letters indicate statistically significant differences (P < 0.05). 0%, 1%, 3%, 5%, 7% and 10% CNC represent composite films containing 0%, 1%, 3%, 5%, 7% and 10% CNC, respectively.
[0088] Depend on Figure 5 As shown in the figure, compared with the pure CMC film, the WVP of the 7% and 10% CNC composite films decreased by 18.2% and 26.3%, respectively. The interaction between CNC and CMC molecules forms hydrogen bonds, which increases the torsion of the film and makes the structure more compact, thereby improving the barrier properties of the film and making it difficult for water vapor to pass through the composite film. In addition, CNC is evenly dispersed in the CMC matrix, and the diffusion path of water molecules becomes tortuous and extended, resulting in a significant reduction in the WVP of the composite film.
[0089] Test item 2: Antibacterial effect of DSWE.
[0090] Samples were prepared according to Example 7, and the inhibitory effect of DSWE on Penicillium expansum and Fusarium oxysporum was analyzed.
[0091] Depend on Figure 6 As shown in (A), the inhibition rate of 10% DSWE on the growth of Penicillium expansum hyphae reached 100%, which was not significantly different from the inhibition rate of 75% ethanol on the growth of Penicillium expansum hyphae. Figure 6(B) After 3 days of dark culture, the growth of Penicillium expansum in 0.25% DSWE medium was significantly inhibited compared with that in lower concentration DSWE medium. However, when the DSWE concentration continued to increase, there was no growth of Penicillium expansum in the medium, indicating that 0.5% was the MIC of DSWE.
[0092] from Figure 7 As can be seen in (A), DSWE has a certain inhibitory effect on Fusarium oxysporum. On the sixth day, the colony diameter of Fusarium oxysporum treated with DSWE decreased by 67.5% compared with the colony diameter of 0% DSWE. Figure 7 In (B), compared with the Fusarium oxysporum on the 0% DSWE plate, the radial growth of Fusarium oxysporum on the 0.4% DSWE plate was very slow, and the hyphae only grew evenly on the sixth day. The colony diameter only grew by 2 mm compared with the second day. Therefore, DSWE has a significant inhibitory effect on Fusarium oxysporum.
[0093] Test Item 3: Analysis of the preservation performance of DSWE-CNC coating.
[0094] The samples were prepared according to Example 8, and the freshness-keeping performance of the DSWE-CNC coating was analyzed.
[0095] As a stone fruit, the color change of apple is the result of the synthesis of anthocyanins and carotenoids during the ripening and maturation process. Figure 8 As can be seen from (A) to (C) in the figure, the color difference between CG and DCCG is significantly reduced compared with CK. The coating reduces the color change of apples, which is mainly because the coating inhibits respiration and limits the oxygen supply in the fruit, thereby reducing the activity of key enzymes in anthocyanin synthesis and key enzymes that catalyze carotenoid synthesis. Figure 8 In (E), on the fifth day, the weight loss rate of the fruit was reduced by the coating treatment, which was attributed to the barrier properties of the coating, which made it difficult for water vapor to diffuse out. Figure 8 In (F), compared with CK, the soluble solid content of DCCG increased by 21.2% on the tenth day. Figure 8 (G) Compared with the fifth day, the titratable acid content in DCCG decreased by only 10.7% on the tenth day, while that in the CK group decreased by 25%. It can be seen that the coating can reduce fruit metabolism and delay the decomposition of starch, thereby maintaining the content of soluble solids during fruit storage. Titratable acid is related to organic acid. When organic acid is used as the main substrate for respiration and other metabolic processes, titratable acid will decrease. Therefore, the barrier properties of the coating can minimize the consumption of organic acid.
[0096] Depend on Figure 8(D), the total phenolic content of CK and CG on the tenth day decreased by 34.1% and 20.22% compared with DCCG, respectively. Oligosaccharides can maintain the quality of fruit. For example, chitosan oligosaccharides are used for postharvest preservation of peaches, which significantly increases the total phenolic substances, flavonoids and lignin content of peach fruits during storage. Pectin oligosaccharides can significantly increase the total phenolic and anthocyanin content of strawberry fruits and improve the quality. The full component analysis of DSWE shows that DSWE contains oligosaccharides such as D-trehalose and α-lactose, which may increase the total phenolic content of apples and improve the quality of apples. In addition, Figure 8 In (H), this study found that the softening speed of fruits coated with film would be reduced. The hardness of DCCG on the tenth day increased by 18.1% compared with the control group, and there was no significant difference with the fresh group (untreated apples). The softening of fruits is related to the modification of cell walls during the ripening process of fruits. The metabolism and enzyme activity of fruits coated with film are inhibited, thereby delaying the degradation process of cell wall components.
[0097] Therefore, the application of coatings with antimicrobial activity can delay the postharvest ripening process of apple fruits, reduce quality losses, and extend the shelf life of apple fruits.
[0098] Test item 4: Antibacterial properties of DSWE-CNC coating.
[0099] The samples were prepared according to Example 9, and the antibacterial properties of the DSWE-CNC coating were analyzed.
[0100] from Fig. 9 It can be seen from (A) to (B) (the columns from left to right are PC, NC, 0% DSWE group, 2% DSWE group, 4% DSWE group, and 10% DSWE group) that the film-forming liquid without DSWE and the film-forming liquid containing different concentrations of DSWE can delay and reduce the incidence and severity of apple Penicillium. Compared with NC, the diameter of the lesions of apples treated with the film-forming liquid of the 0% DSWE group, the 2%, 4% and 10% DSWE groups, and the DSWE-CNC film-forming liquid of the 10% DSWE group decreased by 7%, 67%, 86% and 100% on the 5th day, respectively; and on the 5th day, the incidence of apples treated with the DSWE-CNC film-forming liquid of the 4% and 10% DSWE groups decreased by 66.7% and 100%. On the 3rd, 4th and 5th days, the apples treated with the DSWE-CNC film-forming liquid of the 10% DSWE group did not get sick, which shows that the DSWE-CNC film-forming liquid of the 10% DSWE group has a significant antibacterial effect on Penicillium expansum.
[0101] The inhibition of the film-forming liquid of the 0% DSWE group on apple blue mold is mainly due to the fact that nanomaterials can cause ROS accumulation, membrane damage, enzyme activity loss and protein disorder of pathogenic bacteria, and CNC has biological activities such as controlling intracellular growth factor activity, antiviral and antifungal after sulfonation. On this basis, the DSWE-CNC film-forming liquid has a better inhibitory effect on apple blue mold, which is due to the porous form and a large number of active hydroxyl groups in the CNC structure, resulting in the modification of DSWE with antifungal properties on its surface, thus having antifungal ability and biocompatibility.
[0102] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a durian shell active ingredient nanocellulose antibacterial fresh-keeping coating, characterized in that: The following steps are involved: Taking durian shells, drying them, and making durian shell powder; The durian shell powder is treated by water extraction, and the supernatant is freeze-dried to obtain a water extract powder containing active ingredients of the durian shell; The precipitate obtained after the durian shell powder is treated by alkaline washing and water extraction is collected, freeze-dried, bleached, washed with water until neutral, and dried to obtain durian shell cellulose; the durian shell cellulose is treated by acid hydrolysis to obtain a precipitate, the precipitate is dispersed in water, dialyzed until neutral, ultrasonically treated, and freeze-dried to obtain nanocellulose powder; Take sodium hydroxymethyl cellulose, add water, glycerol, and nanocellulose powder in sequence, and stir continuously at 70°C for 2 h to obtain the first film-forming solution; The water extract powder containing the active ingredient of durian shell is added to the first film-forming liquid at a solid-liquid ratio of 0.02-0.10 g / mL, and the mixture is continuously stirred at 70°C for 10 minutes to obtain the second film-forming liquid, and the film is prepared to obtain the antibacterial and fresh-keeping coating of nanocellulose containing the active ingredient of durian shell; The ratio of sodium hydroxymethyl cellulose, water, glycerin and nanocellulose powder is 1 g: 500 mL: 0.3 g: 0.01-0.1 g.
2. The preparation method according to claim 1, characterized in that: The alkaline washing is specifically as follows: adding the precipitate obtained after treating the durian shell powder with water extraction to a NaOH solution with a concentration of 0.04 g / mL, water bathing at 90°C, and continuously stirring for 2 hours, collecting the precipitate, washing with water, filtering, and centrifuging to remove excess alkali solution, and collecting the precipitate; repeating the above process until the supernatant after centrifugation is colorless; the concentration of the durian shell powder in the NaOH solution is 0.04 g / mL.
3. The preparation method according to claim 1, characterized in that: The bleaching is specifically as follows: adding the dried precipitate to the bleaching solution, placing in a water bath at 80° C., continuously stirring for 2 h, filtering, and collecting the precipitate; repeating the above process until the precipitate is white; the concentration of the dried precipitate in the bleaching solution is 0.04 g / mL.
4. The preparation method according to claim 3, characterized in that: The bleaching solution consists of 0.017 g / mL NaClO, 0.027 g / mL NaOH, and 0.075 g / mL glacial acetic acid.
5. The preparation method according to claim 1, characterized in that: The acid hydrolysis method is specifically as follows: adding durian shell cellulose to a sulfuric acid solution with a volume concentration of 62% so that the concentration of the durian shell cellulose in the sulfuric acid solution is 0.067 g / mL, hydrolyzing in a 45° C. water bath for 30 min; adding water to terminate the reaction, centrifuging, and collecting the precipitate.
6. The preparation method according to claim 1, characterized in that: The ultrasonic treatment was carried out in an ice water bath with a power of 600 W for 60 min, with an ultrasonic start time of 1 s and a stop time of 1 s.
7. The preparation method according to claim 1, characterized in that: The freeze drying of the supernatant is specifically performed by freezing at -80°C for 12 h and then drying in a freeze dryer for 48 h.
8. The preparation method according to claim 1, characterized in that: The method comprises the following steps: treating durian shell powder with water extraction, freeze drying, and obtaining a water extract powder containing active ingredients of durian shell, specifically: adding water to the durian shell powder so that the solid-liquid ratio of durian shell powder to water is 1g:55ml, extracting in a water bath at 90°C for 1 hour, and then ultrasonicating at 90°C and 100W for 90 minutes; centrifuging, collecting the supernatant, filtering to obtain a filtrate, rotary evaporating at 70°C for at least 1 hour until no water vapor is evaporated; freezing at -80°C for 12 hours, and then drying in a freeze dryer for 48 hours to obtain a water extract powder containing active ingredients of durian shell.
9. An antibacterial and fresh-keeping coating film of nanocellulose containing active ingredients from durian shells prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Nano-cellulose edible coatings and uses thereof
US20160002483A1